An evaluation of a logbook for trainees in accident and emergency medicine in the United Kingdom. Issue 2 (June 1991) - Luke, C; Kadzombe, E; Armstrong, A; Gorman, D; Horner, J
Abstract : The ideal requirements of a logbook for trainees in accident and emergency medicine in the United Kingdom were sought by means of a postal survey of 100 Senior Registrars and recently-appointed Consultants in the specialty. Sixty-two replies were received. An overwhelming majority supported ACLS and ATLS certification, as well as formal training in Management/Clinical Budgeting skills, the use of Information Technology, dealing with medicolegal issues and Disaster Planning. Secondments to General Practice, Regional Poisons Centres and the Emergency Services were similarly recommended. A total of 71% (42 responders) approved of a minimum of 3 years experience in an A&E Department before appointment as a Senior Registrar in the specialty. The majority of responders disapproved of acquiring laboratory-based skills. The results of the survey are discussed and suggestions for the possible role of a logbook are made.